Urgensi Penyusunan Nilai Kerawanan Kejahatan Obat dan Makanan sebagai Basis Data dalam Penyelenggaraan Redesain Sistem Perencanaan Penindakan - Fauziah, Pepi; Wibowo, Andi; Dwi Anggraeni Puspa Handoko, Yulian; Indriyana, Indriyana (Eruditio : Indonesia Journal of Food and Drug Safety, 2025)
Referring to the previous 2020-2024 RPJMN period, it has been identified that the existing court decision indicators for convictions do not encompass all functions within the Deputy of Law Enforcement of The Indonesian Food and Drug Authority (Indonesian FDA), thereby failing to holistically represent the effectiveness of law enforcement against drug and food crimes. One strategic activity not reflected in these indicators is the crime vulnerability mapping function within the Law Enforcement Dashboard (ADP). However, the crime vulnerability mapping system remains limited due to its inability to assign weighted values based on the accuracy of information during data input. Addressing this issue, a study was conducted to develop a crime vulnerability score for drug and food crimes based on information source criteria, serving as a proposed consideration for designing performance indicators for the upcoming RPJMN period. Employing a mixed-methods approach, the study utilized quantitative methods through Analytical Hierarchy Process (AHP) and qualitative methods through surveys, involving 33 respondents from diverse backgrounds. The findings revealed that the highest-weighted information source criteria in assessing crime vulnerability were Investigation Results on Drugs and Food (0.225), Intelligence Operations Results on Drugs and Food (0.150), and Surveillance Results on Drugs and Food (0.141). These findings can be further elaborated through broader surveys involving experts in drug and food crime prevention, enabling the proposed "Drug and Food Crime Vulnerability Index" to be advanced as an output indicator for the Indonesian FDA Law Enforcement program objectives.